A Network of Hydrophobic Residues Impeding Helix αC Rotation Maintains Latency of Kinase Gcn2, Which Phosphorylates the α Subunit of Translation Initiation Factor 2 - Gárriz, Andrés (2009)
Kinase Gcn2 is activated by amino acid starvation and down-regulates translation initiation by phosphorylating eIF2á. The Gcn2 kinase domain (KD) is inert and must be activated by tRNA binding to the adjacent regulatory domain. Previous work indicated that yeast Gcn2 latency results from inflexibility of the hinge connecting N- and C-lobes and a partially obstructed ATP-binding site. Here we provide strong evidence that a network of hydrophobic interactions centered on Leu-856 also promotes latency by constraining helix áC rotation, in a manner relieved during amino acid starvation by tRNA binding and autophosphorylation of Thr-882 in the activation loop. Thus, we show that mutationally disrupting the hydrophobic network in various ways constitutively activates eIF2á phosphorylation in vivo and bypasses the requirement for a key tRNA binding motif (m2) and Thr-882 in Gcn2. In particular,  replacing Leu-856 with any non-hydrophobic residue activates Gcn2, while substitutions with various hydrophobic residues maintain kinase latency. We further provide strong evidence that parallel, back-to back dimerization of the KD is a step on the Gcn2 activation pathway promoted by tRNA binding and  autophosphorylation. Remarkably, mutations that disrupt the L856-hydrophobic network or enhance  hinge flexibility eliminate the need for the conserved salt-bridge at the parallel dimer interface, implying  that KD dimerization facilitates reorientation of áC and remodeling of the active site for enhanced ATP  binding and catalysis. We propose that hinge remodeling, parallel dimerization, and reorientation of áC  are mutually reinforcing conformational transitions stimulated by tRNA binding and secured by the  ensuing autophosphorylation of T882 for stable kinase activation.